Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.2307/1511059
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Classroom Assignment Routine for Inclusive Settings

Abstract: This study had two purposes: (a) to identify the characteristics of high-quality classroom assignments and how they are best explained, as indicated by teachers, students with learning disabilities (LD), and students without LD; and (b) to determine the effects of training teachers to use an assignment completion routine based on these characteristics. Multiple-probe and comparison-group designs were used in combination to show the effects of learning the routine on the teachers' planning, explanation, and eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Yet, in studies in which teachers were trained how to implement such adaptations, positive results were observed in their implementation of curricular adaptations (Scott et al, 1998). For example, teachers have been taught to successfully implement instructional adaptations found to be effective for students with disabilities, including clear directions, appropriate, immediate feedback, and mnemonic recall strategies and have reported high levels of satisfaction with these adaptations (Bulgren, Deshler, & Schumaker, 1997;Rademacher, Schumaker, & Deshler, 1996). General educators have been taught to effectively implement instructional adaptations in mathematics (Woodward & Baxter, 1997) and reading and writing (Vaughn, Hughes, Schumm, & Klingner, 1998).…”
Section: Instructional Adaptationsmentioning
confidence: 99%
“…Yet, in studies in which teachers were trained how to implement such adaptations, positive results were observed in their implementation of curricular adaptations (Scott et al, 1998). For example, teachers have been taught to successfully implement instructional adaptations found to be effective for students with disabilities, including clear directions, appropriate, immediate feedback, and mnemonic recall strategies and have reported high levels of satisfaction with these adaptations (Bulgren, Deshler, & Schumaker, 1997;Rademacher, Schumaker, & Deshler, 1996). General educators have been taught to effectively implement instructional adaptations in mathematics (Woodward & Baxter, 1997) and reading and writing (Vaughn, Hughes, Schumm, & Klingner, 1998).…”
Section: Instructional Adaptationsmentioning
confidence: 99%
“…Nor did we include stud-ies about students' perceptions of resource room instruction only (e.g., we did not include Guterman's 1995 study of high school students' views about the effectiveness of their pull-out programs). When an article clearly included multiple components, some of which fit our criteria and some of which did not, we included only the relevant portions of the article (e.g., we included the section on students' perceptions of how teachers give assignments from Rademacher, Schumaker, & Deshler, 1996, but not the section on teachers' perceptions).…”
Section: Fall 1999mentioning
confidence: 99%
“…When multiple purposes, sets of participants, measures, and results were included in an article, only those that pertained to this synthesis were included in our analysis. For example, with the Rademacher, et al (1996) study that included teachers' as well as students' perceptions, we only included information about students; we omitted the description of the teachers, the interview used to assess teachers' views, and teachers' perceptions because they did not address the purpose and criteria for this synthesis.…”
Section: Analysis Proceduresmentioning
confidence: 99%
“…In order to provide acceptable options to students, teachers might rely on information they gather from student interest surveys (Vance, 1995), learning-style preferences (McCarthy, 1996), multiple intelligence theory (Lazear, 1991), and motivation theory (Brophy, 1987); or, teachers might ask the students themselves what they believe are the characteristics of a good assignment. For example, Rademacher, Schumaker, and Deshler (1996) reported that, in addition to variety and choice, students prefer assignments that (a) offer the appropriate level of challenge, (b) allow students to be creative, (c) promote interaction among learners, and (d) provide complete directions. Directions are considered to be complete when they include action steps to be taken to do the work, needed supplies and resources, the due date, and the grading criteria on which the work will be judged. Students also enjoy working in small teams with the teacher in order to plan interesting assignments for the entire class (Rademacher, Cowart, Sparks, & Chism, 1997).…”
Section: Planningmentioning
confidence: 99%